EFEKTIVITAS PELAKSANAAN PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN ( PUAP) DI DESA SIKIJANG KECAMTAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Siska Dian Pratiwi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Effective implementation of the development of agribusiness, rural (PUAP) will work properly if supported by both the human resources, the effectiveness of PUAP aims to improve the social economic community in the village Sikijang, but there are several factors inhibiting the implementation of PUAP so that execution was not in accordance with the rules as well as the implementation of the previously agreed upon. The research objective yaiti first, to find out how the effectiveness of the policy PUAP (Rural Agribusiness Development) in the village of Sikijang District of Logas Tanah Darat Regency Kuantan Singingi Year 2008-2015, Second to determine the inhibiting factors in the implementation of policies PUAP (Rural Agribusiness Development) in 208-2015. this type of research uses qualitative method with descriptive approach. The location of this research uses qualitative method with descriptive approach. The location of this research was conducted at the sub-district Sikijang Logas Tanah Darat Singingi Kuantan District. Data was collected by means of the Impforman and direct observation. While the analysis of data using qualitative methods to analyze data used logic argument based on the data obtained in the field by developing facts and data from imformasi. The results of the research that is done to the group Gapoktan Light farmer in the village of Sikijang in view of the target realization of the loan, the reach of the loan, the percentage of arrears indicates lack of effective Dana PUAP distributed to group members Cahaya Tani village Sikijang, when seen from a limiting factor based on the Minister of Agriculture No: 16 / Permentan / OT. 140/2/2008. That the lack of effective inhibiting factor PUAP fund, Endless contract of PMT, not active extension of the district, this is due to lack of awareness member Gapoktan in refunding PUAP, insprastruktur inadequate. views of these factors in because funds for Extension and ineffective supervision so that the process of Effectiveness of funds PUAP as supporting the economy has not fully succeeded in the Village District of Logas Tanah Darat Sikijang Regency Kuantan Singningi the Year 2008-2015.Keywords: Effectiveness, Program